(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
This paper explores the balance between technical expertise and soft skills required for successful engineering leadership. While strong technical knowledge is crucial, the research will investigate the importance of communication, teamwork, and strategic thinking for leading engineering teams. The paper will analyze real-world case studies or conduct surveys to understand the relative importance of each skill set and propose strategies for fostering well-rounded leaders in the engineering field.